Psycholinguistic analysis of persuasive effectiveness in court speeches: theoretical foundations and linguistic aspects - O. P. Lyaska; V. S. Kshevetskyi (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to the psycholinguistic analysis of the persuasive effectiveness of court speeches, in particular, the theoretical foundations and linguistic aspects of this process. The key elements of language used in court discourse are considered, with an emphasis on their influence on the thoughts, emotions and decisions of the participants in the process.